Data acquisition of flow sensor based to measure water flow in underground drainage - Wirama, I Made Adiswara; Widodo, Rusminto Tjatur; Al Rasyid, Muhammad Udin Harun; Oktavianto, Hary (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
This research focuses on water flow sensors in underground drainage. In Indonesia, the use of sensors and actuators to control and measure water velocity and water discharge in underground drainage is not very popular, although one of the causes of flooding is caused by clogged drainage or workers forgetting to turn on the pump at a certain height and water flow. This paper will explain how to find out the speed and discharge of water in an underground drainage without checking it directly on site. The water flow sensor is used to measure the water velocity and water discharge entering a drainage system. The data acquisition conducted with 3 section, data preparation, data collecting, and data processing. Data preparation is preparing the microcontroller, sensor, and data display to get the data. Data collecting is about collecting the data from sensor in this research the data collected is in pulse that can be calculated to water discharge and water velocity in the data processing. From the experiment, it can be seen that the highest error rate on the sensor is 7.64% and the lowest at 0% or no error with the average amount of error is 2.46%. The data obtained from the sensor can be converted into water velocity and water discharge depending on the shape of the drainage. The length, width and height of the drainage are assumed to be 10x4x3 m respectively, with a constant water level of 2 m, so the water flow sensor is placed at a height of 1 m because the safe height is 1 m. From the case study conducted the error rate of the water flow sensor error is 0%, because the case study conducted using imaginary data. Based from this, the knowledge gained from the research, it can be used to determine the water velocity and water discharge value of underground drainage using water flow sensor, which is expected to be applied to pump houses to more easily determine the state of drainage.